Neonatal Hemodynamics: From Developmental Physiology to Comprehensive Monitoring - Vrancken, Sabine L.; van Heijst, Arno F.; de Boode, Willem P. (Frontiers in Pediatrics, 2018)
Maintenance of neonatal circulatory homeostasis is a real challenge, due to the complex physiology during postnatal transition and the inherent immaturity of the cardiovascular system and other relevant organs. It is known that abnormal cardiovascular function during the neonatal period is associated with increased severe morbidity and mortality. Understanding the functional and structural characteristics of neonatal circulation is therefore essential, as therapeutic hemodynamic interventions should be based on assumed underlying (patho)physiology. The clinical assessment of systemic blood flow by indirect parameters, such as blood pressure, capillary refill time, heart rate, urine output and central-peripheral temperature difference is inaccurate. As blood pressure is no surrogate for systemic blood flow, information on cardiac output and systemic vascular resistance should be obtained in combination with an evaluation of end organ perfusion. Accurate and reliable hemodynamic monitoring systems are required to detect inadequate tissue perfusion and oxygenation at an early stage, before this results in irreversible damage. Also, the hemodynamic response to the initiated treatment should be re-evaluated regularly as changes in cardiovascular function can occur quickly. We review new insights in the understanding of cardiovascular physiology (during and after transition) and discuss methods for current and future neonatal cardiovascular monitoring.